Planejamento urbano, poder judiciário e participação popular: estudos de caso sobre a judicialização de processos de revisão de planos diretores - Oliveira, Bruno de Sousa (2019)
The Master Plan is a basic instrument of urban development policy assigned by the Federal Constitution of 1988. Considering this, the present work aimed to analyze how the Judiciary Power decides, according to each city’s democratic management and popular participation contained in Law No. 10.257 / 01 (City Statute), on the guarantee of popular participation in the modification processes of Master Plan. To this end, an analysis of lawsuits in the cities of Fortaleza (CE), São Paulo (SP) and Palmas (TO) was proceeded. These specific cases were chosen based on the availability of case files and the different dimensions of the three cities, which contributes to the diversity within the analysis. Therefore, this study follows the qualitative method with the use of bibliographical, statutory, documentary and non-participatory observation. The aim was to understand the conformation of Master Plans in the Brazilian Urban Planning history and its current participatory configuration. The potential relations between the Judiciary Power, Urban Planning and Participatory Democracy were also analyzed in the scope of a widening of participatory means and the occurrence of Judicialization and Judicial Activism phenomena in the Judiciary Power after the 1988 Constitution. In the cases studied, despite the Judiciary opportunities to guarantee popular participation in the revision processes of Master Plans, aspects such as slowness and formalism in the content analysis of popular participation can make it difficult for lawsuits to be effective.